Redefinisi Kepatuhan Halal Berbasis Maqasid al-Syari’ah: Menjawab Tantangan Sustainable Consumption dan Kebijakan Afirmatif UMK 2025 - Fikri Zainun Nasihin (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2025)
The 2025 free halal certification policy accelerates legality for Micro and Small Enterprises (MSEs) but risks reducing halal to mere administrative compliance. Unlike previous studies focusing on marketing, this research highlights the critical gap between technical regulations and the challenges of sustainability and novel food safety. This study aims to redefine MSEs' halal compliance by integrating the Maqasid al-Syari’ah framework. Using a critical conceptual review method, this study finds that the self-declare model requires strengthened ethical literacy. The results formulate a substantive compliance framework that pursues not only certificate legality but also internalizes the protection of life (hifz an-nafs) from hazardous ingredients and environmental protection (hifz al-bi’ah). Policy implications suggest that BPJPH should revise halal supervision training materials to include food safety and sustainability indicators, ensuring the 2025 halal ecosystem excels in both quantity and ethical quality